2006
DOI: 10.1373/clinchem.2006.071142
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting S-Homocysteinylation of LDL Apoprotein B

Abstract: Background: Hyperhomocysteinemia is an important risk factor for vascular disease and atherosclerosis, but the mechanisms by which homocysteine exerts its deleterious effects are not known. Because oxidation and/or homocysteinylation may increase atherogenicity of LDL, we investigated S-homocysteinylation of LDL as a possible contributor to atherosclerosis pathogenesis. Methods: We used capillary electrophoresis to measure LDL-bound thiols [homocysteine, cysteine (Cys), cysteinylglycine, glutathione, and gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 30 publications
(35 reference statements)
4
26
0
1
Order By: Relevance
“…By multiple regression analysis it also emerged that, as for the normal population, Cys-Gly seemed to inhibit the interaction between Hcy and LDL also in CKD, thus confirming our previous hypothesis on the possible protective role of this molecule toward the proatherogenic modification of LDL [22,23]. We found that the relative quantity of Cys-Gly is higher in the apoprotein fraction than in plasma both in controls and CKD patients, thus confirming our previous data on the high affinity of apoB for Cys-Gly.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…By multiple regression analysis it also emerged that, as for the normal population, Cys-Gly seemed to inhibit the interaction between Hcy and LDL also in CKD, thus confirming our previous hypothesis on the possible protective role of this molecule toward the proatherogenic modification of LDL [22,23]. We found that the relative quantity of Cys-Gly is higher in the apoprotein fraction than in plasma both in controls and CKD patients, thus confirming our previous data on the high affinity of apoB for Cys-Gly.…”
Section: Discussionsupporting
confidence: 81%
“…Fibronectin and factor Va are examples of plasma proteins that undergo S-linked homocysteinylation with possible functional consequences. We have recently demonstrated that plasma lipoproteins are also susceptible to S-homocysteinylation [21,22]. Given that at least 5 low molecular mass aminothiols occur in plasma, Hcy competes with other thiols for binding to the accessible –SH sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…52 Meanwhile, it is an inhibitory neurotransmitter in the brain and an important participant and regulator in glucose metabolism. 53 As a major energy source, alanine might enter tricarboxylic acid (TCA) cycle and glucose in gluconeogenesis.…”
Section: Changes In Energy Metabolismmentioning
confidence: 99%